CURRENT PROBLEMS OF CONDUCTING AND CHORAL CYCLE DISCIPLINES AND THEIR SOLUTIONS IN THE CONDITIONS OF DISTANCE LEARNING - Мержева, Л.Ф. (SWorldJournal, 2022)
The integration of traditional and innovative teaching methods in music education is the most important task of our time. The abstracts reveal the means of using information technology in music education of the disciplines of conducting and choral cycle,